2021
DOI: 10.1097/ico.0000000000002706
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Immune Cells on Donor Corneal Endothelium After Corneal Transplantation Using the HRT-Rostock Cornea Module

Abstract: The aim of this study was to investigate the immune cells on corneal endothelium of the graft in patients who underwent penetrating keratoplasty (PK), Descemet-stripping endothelial keratoplasty (DSEK), and Descemet membrane endothelial keratoplasty (DMEK).Methods: A total of 43 eyes of 43 patients who underwent PK (17 eyes), DSEK (13 eyes), and DMEK (13 eyes) and who did not show any sign of graft rejection were recruited for the study. Patients who underwent cataract surgery (26 eyes) served as controls. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
4
0
3
Order By: Relevance
“…Repeat keratoplasty procedures (PKP and posterior lamellar keratoplasty) showed increased cell densities on the endothelium compared to primary keratoplasty procedures, while again there were no differences in flare. From this, the authors concluded that in both cases, the presence of immune cells on the corneal endothelium is not primarily due to BAB damage [20].…”
Section: Laser Flare Photometry and Posterior Lamellar Keratoplastymentioning
confidence: 86%
See 3 more Smart Citations
“…Repeat keratoplasty procedures (PKP and posterior lamellar keratoplasty) showed increased cell densities on the endothelium compared to primary keratoplasty procedures, while again there were no differences in flare. From this, the authors concluded that in both cases, the presence of immune cells on the corneal endothelium is not primarily due to BAB damage [20].…”
Section: Laser Flare Photometry and Posterior Lamellar Keratoplastymentioning
confidence: 86%
“…A study by Okumura and colleagues investigated BAB dysfunction as a possible cause of immune cells on the endothelium after keratoplasty (detected with the HRT Rostock Corneal Module) without a recognizable rejection reaction. This study with a comparatively small cohort did not find any significant differences in flare measurements in eyes after PKP (17 eyes, 27.7 ± 31.8 months postop), posterior lamellar keratoplasty [DSEK (13 eyes, 20.3 ± 20.3 months postop)], and DMEK (13 eyes, 11.2 ± 8.4 months postop) compared to controls (26 eyes after cataract surgery), although a trend towards higher flare values was observed in some patients in the PKP group [20]. Neither was there any correlation between the density of the immune cells and the flare.…”
Section: Laser Flare Photometry and Posterior Lamellar Keratoplastymentioning
confidence: 99%
See 2 more Smart Citations
“…They are less commonly available, are challenging to use, and the findings are not very specific to rejection. 60 Their utility comes up when suspecting viral etiologies in these eyes. They can pick up certain particular features like owl’s-eye endothelial cells, which are suggestive of CMV endotheliitis.…”
Section: Diagnosis Of Descemet Membrane Endothelial Keratoplasty Reje...mentioning
confidence: 99%